The Role of Artificial Intelligence (AI) as Learning Style Master of Student in Digital Era - Nabila, Nisa Afrinauly; Hermawati, Kiki Ayu; Mariana, Mela (Proceeding International Conference on Religion, Science and Education, 2024)
Artificial Intelligence (AI) is the one of popular technology in the world of education in the digital era. AI is a system used to imitate human intelligence or dead object with the use of sophisticated technology to accomplish human cognitive problems. But the usage of AI has a significant impact that is problems of privacy and data security, as well as ethics and society. Because of this, the usage of AI has to do wise and precise to produce a maximum advantage for improving education. The article aims to analyze the role of AI in helping student assignments. This research used a descriptive qualitative approach and the data was reached by a Google form questionnaire. This research used data from a questionnaire via Google form given to the master of student Islamic Education UIN Sunan Kalijaga Yogyakarta semester 1 2022/2023. , the data was obtained via Google form and then, the link was disseminated by Whatsapp. The primary data of research earned by Google from respondents. The data analysis used a statistical description. Referring to the technique, the researcher only describes the data that has been collected without the intention of concluding. The result showed 73,4% of respondents used AI for doing assignments, and 26.7% of respondents used not AI for doing assignments.